Sleeve Pneumatic Artificial Muscles for Antagonistically Actuated Joints - Kelly, Kevin; Mc Ginn, Conor; CULLINAN, MICHAEL (My University, 2019)
Pneumatic artificial muscles (PAMs) have been researched for applications in powered exoskeletons, orthosis and robotics. Their high force to mass ratio, low cost and inherent compliance are particularly advantageous for systems requiring physical interaction with humans. Sleeve PAMs, which introduce an internal structure to the actuator, offer improved force capacity, contraction ratio, efficiency and operating bandwidth. In this paper sleeve PAMs are applied to a popular muscle configuration; that of a joint operated antagonistically by two muscles. It is shown that the sleeve PAM can increases the range of joint rotation by 14% or load capacity by over 50% of that of a comparable joint actuated with traditional PAMs, depending on the joint configuration.The stiffness of joints actuated with both PAM types is also studied, particularly the case of closed system operation (mass of air in the PAMs is constant), where the reduced volume of the sleeve PAM significantly increases the observed stiffness. Finally energy consumption is considered, showing substantial savings in the case of joints actuated with sleeve PAMs.
IEEE Transactions
2019 International Conference on Robotics and Automation (ICRA)
PUBLISHED
Palais des congres de Montreal, Montreal, Canada
Keywords: Robotics; Pneumatic artificial muscles; PAMs; Exoskeletons; Orthosis; Joints; Ageing